The efficacy of core decompression combined with regenerative therapy in early femoral head necrosis: a systematic review and meta-analysis involving 954 subjects - Haiwei Tang; Tingxian Ling; Enze Zhao; Mingke You; Xi Chen; Gang Chen; Kai Zhou; Zongke Zhou (Frontiers in Pharmacology)
BackgroundThe debate continues on whether combining core decompression (CD) with regenerative therapy provides a more effective treatment for early femoral head necrosis than CD alone. This systematic review and meta-analysis endeavored to assess its efficacy.MethodsWe systematically searched PubMed, Web of Science, and Cochrane Library through July 2024 for RCTs and cohort studies evaluating the impact of core decompression (CD) with regenerative therapy versus CD alone in early-stage osteonecrosis (ARCO I, II or IIIa or Ficat I or II) of the femoral head (ONFH). Bias was evaluated using the Cochrane ROB 2.0 for RCTs and the Newcastle-Ottawa Scale (NOS) for cohort studies. The primary outcome was disease progression, measured by the incidence of staging advancement and total hip arthroplasty (THA) conversion. Clinical outcomes, including VAS, HHS, WOMAC, and Lequesne index, were secondary measures. Subgroup analyses were performed for variables such as age, BMI, follow-up period, and dosage in the bone marrow aspirate concentrate (BMAC) group, with results depicted in forest plots.ResultsThis study represented a total of seven RCTs (mean follow-up time 36.57 months) and eight cohort trials (mean follow-up time 74.18 months) involving 954 hips. CD, when combined with agents, exhibited considerably enhanced efficacy over CD alone (risk ratio (RR) = 0.55 (95% CI 0.39–0.77), p < 0.001, I2 = 54%) and 0.59 (95% CI 0.43–0.81), p = 0.001, I2 = 51%), respectively). However, a significant difference was exclusive to the CD combined with BMAC group in terms of stage progression outcomes (stage progression, RR = 0.47 (95% CI 0.28–0.78), p = 0.004, I2 = 67%); THA conversions, RR = 0.41 (95% CI 0.32–0.52), p < 0.001, I2 = 43%). Secondary outcomes (VAS, HHS, WOMAC score and Lequesne index) showed improved results when CD was combined with other regenerative agents, such as bone mesenchymal stem cells (BMSCs) and bone morphogenetic proteins (BMPs), etc. In the reported data, the regenerative group demonstrated significantly higher rates of subjective improvement in pain and functional outcomes compared to those in the CD group (71.74% (66/92) vs. 56.38% (53/94). Subgroup analysis revealed superior outcomes in the low-dose (less than 20 mL) BMAC group and patients aged under 40 years old in stage progression rate and THA conversion rate.ConclusionCD, when combined with regenerative therapy, can diminish hip pain and enhance functionality, but its ability to slow disease progression remains uncertain. BMAC presents a more substantiated efficacy evidence than other agents, with low-doses of BMAC in patients under 40 years potentially slowing ONFH progression. Nonetheless, the high heterogeneity and relatively short follow-up time of these studies make it difficult to draw accurate conclusions, which necessitates verification through future trials comparing CD versus CD combined with regenerative therapy, with a focus on extended follow-up periods.Systematic Review Registrationidentifier CRD42023467873.